Placental Infection by Salmonella Typhimurium in a Murine Model: The Role of Innate Immune Mediators in Cell Death at the Fetal-Maternal Interface - Wachholz, Kristina Lora Catherine (Université d'Ottawa / University of Ottawa, 2016)
Maternal tolerance during pregnancy increases the risk of infection with certain intracellular pathogens such as Salmonella enterica serovar Typhimurium (S.Tm). Systemic S.Tm infection during pregnancy in normally resistant 129X1/SvJ mice, with a functional natural resistance-associated macrophage protein-1 (Nramp1), leads to severe placental infection followed by fetal and maternal death. We hypothesized infection-induced inflammatory trophoblast cell death contributes to adverse pregnancy outcomes. We therefore investigated the kinetics of systemic and oral S.Tm infection in wild-type and gene deficient mice with defects in specific inflammatory pathways. Systemic infection with S.Tm resulted in preferential placental replication compared to other tissues in Nramp1+/+ mice. At 24 hours, <25% of individual placentas per mouse were infected, progressively increasing to >75% by 72 hours which correlated with a steady increase in resorption rates. Moreover, placental infection was associated with increased neutrophils, macrophages and natural killer cells whereas neutrophil numbers in the spleen remained unchanged, suggesting dichotomous modulation of inflammation in the systemic compartment compared to the feto-maternal interface. Oral infection resulted in systemic dissemination of the bacteria, substantial placental colonization and fetal loss five days post-infection in C57BL/6J mice. Systemic infection in pregnant cell death deficient Rip3-/-Nramp1+/+ mice (with defective necroptosis) resulted in decreased fetal demise relative to Nramp1+/+ and Caspase-1,11-/-Nramp1+/+ mice (with defective pyroptosis) suggesting a role for necroptotic inflammation. This study provides insight into the kinetics and mechanism of inflammation and cell death during placental S.Tm infection. Such studies may assist in the rational management of foodborne pathogens contracted during pregnancy.
Keywords: Pregnancy; Infection; Immunity; Cell Death; Inflammation; Salmonella